“A CRISE, PARTE I”: O PROCESSO DA PRODUÇÃO DO ÁUDIO DRAMA IMERSIVO COM ÁUDIO BINAURAL - BOAVENTURA, CRISTALL HANNAH ROCHA DA CUNHA BRANDÃO (2020)
In the Brazilian scenario of audio drama production, little mixing techniques have been used for binaural distribution. This report describes the design steps of developing an immersive drama audio product with a binaural panorama. The concepts used address topics such as the definition of sound, binaural audio and sound narrative. We perform all necessary steps for the development of this product. The work proposes an alternative entertainment content, when creating a work with immersive sound narrative, mainly targeting people who have visual impairments.